2011
DOI: 10.1002/hbm.21357
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potential activity in the basal ganglia differentiates rewards from nonrewards: Response to commentary

Abstract: We recently demonstrated that the feedback negativity may be better understood as a reward-related positivity that is absent on nonreward trials, and source localization revealed that this reward response may reflect activity in the striatum. In a commentary on our report, Cohen et al. argue against this latter finding, claiming it is unlikely that the striatum contributes to the scalp-recorded event-related potential. We disagree with the line of reasoning presented by Cohen et al., and we respond here to eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…The ACC and a second potential source in the basal ganglia appear to contribute to the FN in distinct ways, such that the former is associated with increased activity to monetary loss and the latter with increased activity to monetary gain; this interpretation is also consistent with the extant neuroimaging literature (Liu et al, 2011). As with any application of source analysis to ERP data, however, this result should be interpreted with some caution (Cohen et al, 2011a; Foti et al, 2011c) and further substantiated with complementary evidence from depth electrodes and lesion studies. For example, gain-related delta may reflect coordinated frontostriatal activation to rewards rather than a direct contribution of the striatum to the scalp-recorded signal per se.…”
Section: Discussionmentioning
confidence: 61%
“…The ACC and a second potential source in the basal ganglia appear to contribute to the FN in distinct ways, such that the former is associated with increased activity to monetary loss and the latter with increased activity to monetary gain; this interpretation is also consistent with the extant neuroimaging literature (Liu et al, 2011). As with any application of source analysis to ERP data, however, this result should be interpreted with some caution (Cohen et al, 2011a; Foti et al, 2011c) and further substantiated with complementary evidence from depth electrodes and lesion studies. For example, gain-related delta may reflect coordinated frontostriatal activation to rewards rather than a direct contribution of the striatum to the scalp-recorded signal per se.…”
Section: Discussionmentioning
confidence: 61%
“…Several studies localized its origin along the anterior cingulate cortex (Bellebaum and Daum, 2008;Gruendler et al, 2011;Hewig et al, 2007;Mathewson et al, 2008;Miltner et al, 1997;Potts et al, 2006;Zhou et al, 2010). Others found the source rather in the posterior cingulate cortex (Badgaiyan and Posner, 1998;Cohen and Ranganath, 2007;Hewig et al, 2007;Müller et al, 2005;Nieuwenhuis et al, 2005b) or even in the basal ganglia (Carlson et al, 2011;Foti et al, 2011aFoti et al, , 2011bMartin et al, 2009;Nieuwenhuis et al, 2005b). Besides the inconsistent localizations, the methods used in these studies face several limitations when trying to overcome the unsolvable inverse problem (Helmholtz, 1853).…”
Section: Discussionmentioning
confidence: 99%
“…Although many source estimation studies localized the FRN in the large area of the ACC (for review cf Walsh and Anderson, 2012), several studies also located the origin of the FRN in the posterior cingulate cortex (Badgaiyan and Posner, 1998;Cohen and Ranganath, 2007;Hewig et al, 2007;Müller et al, 2005;Nieuwenhuis et al, 2005b). Others (Carlson et al, 2011;Foti et al, 2011aFoti et al, , 2011bMartin et al, 2009;Nieuwenhuis et al, 2005b) found the source within the basal ganglia, which is also known to crucially process RPEs. All source localization studies so far face the unsolvable inverse problem, which states that the same topographical maps measured at the scalp surface can be caused by several different sources and/or source configurations (Helmholtz, 1853).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, while several studies identified the dorsal ACC as the major generator of the FN (Bellebaum & Daum, ; Gehring & Willoughby, ; Holroyd et al., ; Miltner et al., ), several other cortical sources close or more distant to the dorsal ACC have also been reported, including, for example, the rostral ACC and the posterior cingulate (Nieuwenhuis, Slagter et al., ), lateral frontal cortex and temporal sites (Bellebaum & Daum, ), as well as the presupplementary and supplementary motor area (Holroyd, Nieuwenhuis et al., ). Others have even identified subcortical regions (i.e., the striatum) as the main FN source (Foti et al., ), although these findings are not unquestioned (Cohen, Cavanagh, & Slagter, ; also see Foti, Weinberg, Dien, & Hajcak, ). Moreover, single unit recordings in monkeys suggest that there are several functional subpopulations of neurons in the MFC that can code distinct kinds of reward information like outcome favorableness (e.g., Matsumoto, Matsumoto, Abe, & Tanaka, ), recent reward history (e.g., Seo & Lee, ), or unexpectedness of a particular reward (Hayden et al., ).…”
Section: Discussionmentioning
confidence: 99%